PROGRAM DESA INOVASI SEBAGAI UPAYA PERCEPATAN MENUJU DESA MANDIRI DI KABUPATEN CILACAP - Suryo Wibisono; Muhammad Husnul Maab; Purwanto Kurniawan (Jurnal Inovasi Daerah, 2022)
Desa Inovasi Program is an effort of the Cilacap Regency Government to develop rural potential and resources through improving the quality of development planning and implementation in order to improve the welfare and independence of the rural community. Strengthening Desa Inovasi aims to realize independent village management through strengthening the planning sector and local institutions. Desa Inovasi Program is in line with the spirit of realizing an Independent Village in Cilacap Regency. By using a qualitative-descriptive method, the results of the research show that Desa Inovasi Program is quite effective to accelerate towards Desa Mandiri.